Knowledge and skills for life : first results from the OECD Programme for International Student Assessment (PISA) 2000 - (:unkn) unknown (My University, 2001)
"Knowledge and Skills for Life assesses how far students near the end of compulsory education have acquired some of the knowledge and skills that are essential for full participation in society. It presents evidence on student performance in reading, mathematical and scientific literacy, reveals factors that influence the development of these skills at home and at school, and examines what the implications are for policy development. The raport shows considerable variation in levels of knowledge and skills between students, schools and countries. The extent to which the socio-economic background of students and schools affects student performance varies. Some countries have managed to mitigate the influence of social background and some have done that while achieving a high overall mean performance. This is a noteworthy achievement. The OECD Programme for International Student Assessment (PISA) is a collaborative process among the 30 Member countries of the OECD and some non-OECD countries, bringing together scientific expertise from the participating countries and steered jointly by their governments on the basis of shared, policy-driven interests. PISA is an unprecedented attempt to measure student achievement across all OECD countries and some non-OECD countries, as is evident from some of its features:a- The literacy approach: PISA aims to define each domain (reading, mathematics and science) not merely in terms of mastery of the school Curriculum, but in terms of the knowledge and skills needed for full participation in society.n- A long-term commitment: Over the decade to come, it will enable countries regularly and predictably to monitor their progress in meeting key learning objectives.The age-group covered: By assessing 15-year-olds, i.e. young people near the end of their compulsory education, PISA provides a significant indication of the overall performance of school systems.-- The relevance to lifelong learning: PISA does not limit itself to assessing students' knowledge and skills but also asks them to report an their own, self-regulated learning, their motivation to learn and their preferences for different types of learning situation.
Keywords: S 1.1 Allgemeinbildende Schule; S 2.3 Berufsbildungspolitik; L 2.1 Lernformen; G 2.4 Sozialer Wandel; Schulische Qualifikation; Internationaler Vergleich; Schulwesen; Schüler; Jugendlicher; Bildungspolitik; Selbstgesteuertes Lernen; Geschlechtsspezifische Faktoren; Lebenssituation; OECD; 2000-2000